Human papillomavirus vaccination: coverage rate, knowledge, acceptance, and associated factors in college students in mainland China - Che Deng; Xiaoli Chen; Yanqun Liu (Taylor & Francis Group, 2021)
In China, there are about 131,500 new cases of human papillomavirus (HPV) infection every year. However, studies focused on the related cognitions in the general college-going population, who belong to an at-risk age group and are of childbearing age, are relatively limited. Thus, this cross-sectional online survey study, conducted from December 2018 to March 2019, sought to investigate HPV vaccination rates, knowledge, acceptance, and associated factors in this population. Descriptive analysis and ordinal logistic regression analysis were conducted to analyze the factors associated with HPV vaccination intention. A total of 1,029 questionnaires were collected, of which 1,022 were valid (males: 267, females: 755). As per the results, only 3.1% of the sample had been vaccinated against HPV. The overall levels of knowledge about HPV and its vaccination were low. Male students' knowledge about HPV types, infection symptoms, vaccination cycles, and preventable diseases was significantly lower than that of female students. As for acceptance, only 36.9% of females and 24.8% of males indicated that they would choose to undergo HPV vaccination. Chinese college students' knowledge of HPV and its vaccination is limited. More than half of the sample was unsure about undergoing HPV vaccination, with concerns about safety and effectiveness serving as the main barriers. Measures such as strengthening health education, improving vaccination safety and effectiveness, and reducing vaccine prices should be taken to promote HPV vaccination among Chinese college students.